Lemma on the Binomial Coefficients of Combinatorial Geometric Series - Chinnaraji Annamalai; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
This paper presents lemmas and its corollaries on the combinatorial geometric series and summation of series of binomial coefficients. Also, the coefficient for each term in combinatorial geometric series refers to a binomial coefficient. These ideas can enable the scientific researchers to solve the real life problems.